A Healthy Nordic Diet Alters the Plasma Lipidomic Profile in Adults with Features of Metabolic Syndrome in a Multicenter Randomized Dietary Intervention. Issue 4 (9th March 2016) - Lankinen, Maria; Schwab, Ursula; Kolehmainen, Marjukka; Paananen, Jussi; Nygren, Heli; Seppänen-Laakso, Tuulikki; Poutanen, Kaisa; Hyötyläinen, Tuulia; Risérus, Ulf; Savolainen, Markku J; Hukkanen, Janne; Brader, Lea; et al.
Abstract: Background: A healthy Nordic diet is associated with improvements in cardiometabolic risk factors, but the effect on lipidomic profile is not known. Objective: The aim was to investigate how a healthy Nordic diet affects the fasting plasma lipidomic profile in subjects with metabolic syndrome. Methods: Men and women ( n = 200) with features of metabolic syndrome [mean age: 55 y; body mass index (in kg/m 2 ): 31.6] were randomly assigned to either a healthy Nordic ( n = 104) or a control ( n = 96) diet for 18 or 24 wk at 6 centers. Of the participants, 156 completed the study with plasma lipidomic measurements. The healthy Nordic diet consisted of whole grains, fruits, vegetables, berries, vegetable oils and margarines, fish, low-fat milk products, and low-fat meat. An average Nordic diet served as the control diet and included low-fiber cereal products, dairy fat–based spreads, regular-fat milk products, and a limited amount of fruits, vegetables, and berries. Lipidomic profiles were measured at baseline, week 12, and the end of the intervention (18 or 24 wk) by using ultraperformance liquid chromatography mass spectrometry. The effects of the diets on the lipid variables were analyzed with linear mixed-effects models. Data from centers with 18- or 24-wk duration were also analyzed separately. Results: Changes in 21 plasma lipids differed significantly between the groups at week 12 (false discovery rate P < 0.05), including increases in plasmalogens and decreases in ceramides in the healthy Nordic diet group compared with the control group. At the end of the study, changes in lipidomic profiles did not differ between the groups. However, when the intervention lasted 24 wk, changes in 8 plasma lipids that had been identified at 12 wk, including plasmalogens, were sustained. There were no differences in changes in plasma lipids between groups with an intervention of 18 wk. By the dietary biomarker score, adherence to diet did not explain the difference in the results related to the duration of the study. Conclusions: A healthy Nordic diet transiently modified the plasma lipidomic profile, specifically by increasing the concentrations of antioxidative plasmalogens and decreasing insulin resistance-inducing ceramides. This trial was registered at clinicaltrials.gov as NCT00992641.